The THE EFFECT OF EXPERIENCE QUALITY ON RETURN VISIT INTEREST THROUGH PERCEPTION OF VALUE, DESTINATION IMAGE AND SATISFACTION: PENGARUH EXPERIENCE QUALITY TERHADAP MINAT KUNJUNG ULANG MELALUI PERSEPSI NILAI, CITRA DESTINASI DAN KEPUASAN - Saeful Rahmat, Pupu; Harjadi, Dikdik (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The problem in this study is the low interest in revisiting tourist objects Kuningan Botanical Gardens. The research objectives are: (1) to analyze the effect of image destination for repeat visits; (2) analyzing the effect of perceived value on the image of the destination; (3) analyze the effect of satisfaction on destination image; (4) analyzing the effect of experience quality on perceived value; (5) analyze the effect of experience quality on satisfaction; (6) analyze perceived value and image of the destination in mediating the influence of experience quality to interest in repeat visits; (7) analyze the satisfaction and image of the destination in mediate the effect of experience quality on intention to revisit. The research population includes all tourists who have visited the object Kuningan Botanical Garden Tourism (starting as a tourist attraction until now) namely as many as 87,288 visitors. The sampling technique uses sampling incidental (visitors encountered by chance). Determination of the number of samples using the slovin formula with an error rate of 5% so that samples are found as many as 400 tourists. Methods of data analysis using SEM analysis with analysis tool in the form of SmartPLS. The results of the study: (1) destination image has a significant positive effect on interest revisit; (2) perceived value has a significant positive effect on image destination; (3) satisfaction has a positive and significant effect on destination image; (4) experience quality has a positive and significant effect on perceived value; (5) experience quality has a significant positive effect on satisfaction; (6) perception the value and image of the destination are able to mediate the effect of experience quality on interest in repeat visits; (7) satisfaction and destination image are able to mediate influence experience quality on intention to revisit. Keywords: Interest in Repeat Visits; Destination Image; Experience Quality; Perception of value; Satisfaction